Short communication. Changes in the composition of sows milk between days 5 to 26 of lactation - Daza, A.; Riopérez, J.; Centeno, C. (Spanish Journal of Agricultural Research, 2004)
Ten Large White x Landrace sows were used to measure changes during lactation of composition of the milk. Milk composition on day 5, 12, 19 and 26 of lactation included 195.7, 192.2, 185.4 and 184.1 g of dry matter kg-1, 59.3, 55.8, 55.1 and 54.8 g of crude protein kg-1 and 1.3, 1.18, 1.16 and 1.17 Mcal of gross energy kg-1, respectively. Dry matter, crude protein and gross energy levels in the milk did not vary significantly with stage of lactation. Amino acids average total (except tryptophan, proline and cystine) and lysine average contents of sows milk on day 5, 12, 19, and 26 after parturition were 73.5, 77.6, 82.7 and 81.8 g/100 g milk protein and 5.97, 6.41, 7.05 and 6.81 g/100 g milk protein, respectively. All studied amino acids with some exceptions (methionine, threonine, histidine and glycine) varied significantly (P<0.05) its concentration with stage of lactation. The concentration change of some amino acids (lysine, leucine, valine and glutamic acid) found in our experiment could be ascribed to the change, throughout lactation, of the ratio of casein to whey proteins in the milk.